The Polymorphic Linker Domain of pfmdr1 Is Associated with Resistance-Conferring Mutations in Plasmodium falciparum Populations from East and West Africa - Okombo, John (American Society for Microbiology, 2013)
Sequence variation in the asparagine/aspartate-rich domain of pfmdr1 in 215 isolates of Plasmodium falciparum from three African countries was compared with published data. The role of this domain in modulating antimalarial sensitivity has not been established. The pfmdr1 86Y allele was significantly associated with different configurations of the Asn/Asp-rich domain in West and East Africa. In Kenya, a specific form of the Asn/Asp-rich domain was significantly linked to the 86Y, 184Y, and 1246Y haplotype of pfmdr1.